The Effect of Annealing in Controlled Vapor Pressure on the Thermoelectric Properties of RF-Sputtered Bi2Te3 Film - Kim, Hyo-Jung; Yim, Ju-Hyuk; Choi, Won Chel; Park, Chan; Kim, Jin-Sang (SPRINGER, 2012)
To investigate the effect of annealing in controlled atmosphere on the thermoelectric properties of Bi-Te film, Te-deficient Bi-Te film was deposited by sputtering, and then annealed with various Bi-Te alloy powders with different Te concentrations in a closed system at 250A degrees C for 24 h. Bi-Te phases other than Bi2Te3 in the as-deposited film could be removed when the film was annealed with Bi-Te source powder containing 62 at.% or higher content of Te. At the same time, the values of Seebeck coefficient and carrier concentration of the films approach -105 V/K and 3 x 10(19) cm(-3) to 6 x 10(19) cm(-3), respectively. This result indicates that mass transport of Te to the film takes place, resulting in the formation of Bi2Te3 phase and reduction of the amount of -type carriers due to compositional change of the film from Te-deficient to stoichiometric. Annealing in controlled Te-vapor atmosphere is an effective method to improve the thermoelectric properties of Bi-Te film by changing the composition and phase of Te-deficient film to stoichiometric Bi2Te3 film.
Keywords: DEPOSITION